Quality of Work as a Result of AI-based Transformation in The Gaming Sector - Marcin OLKIEWICZ; Adam CZARNOTA; Joanna Alicja DYCZKOWSKA (Communications of International Proceedings, 2025)
The purpose of the study is to demonstrate how AI-based transformation is shaping changes in the quality of work in the gaming industry. The reason for conducting the study was the limited availability of information, in the literature, from the area of work process changes resulting from the implementation and application of AI. The resulting research gap is important because it is determined by changing attitudes, needs, interests of the public, among other things, making the gaming industry grow very rapidly (e.g., in 2024, growth in: the number of paying gamers by 5% generating $1.50 billion in revenue; the number of mobile games by 3%) finding newer and newer stakeholders. This growing volatility supported by the capabilities of artificial intelligence is defining new directions for the industry and significantly affecting the quality of employees and their labor market. The article uses secondary data indicated in reports, reports and other studies dealing with the subject of the research. The trends presented in the article indicate the emerging opportunities for employees, for example, in the use of the accelerator of creativity, experience, openness to change, which increase and use the potential of employees and provide opportunities for personal development while maintaining work-life balance.
Keywords: transformation; artificial intelligence; gaming industry; management